Problems of Long-Term Therapy of Chronic Diseases: Compliance – Refusal of Therapy – Motivation for Treatment - Tashmatova G. A.; Primkulova G. N. (Zien Journals, 2023)
The article discusses the problem of compliance in terms of treatment of patients with chronic diseases. Lack of adherence to therapy (non-compliance) significantly reduces the effectiveness of treatment, and often negates all the efforts of doctors.
Keywords: compliance; patient; chronic diseases; non-compliance